Effect of neuroleptic treatment on involuntary movements and motor performances in Huntington's disease. Issue 8 (August 1984) - Girotti, F; Carella, F; Scigliano, G; Grassi, M P; Soliveri, P; Giovannini, P; Parati, E; Caraceni, T
Abstract : Eighteen patients with Huntington's chorea were examined before and after neuroleptic treatment (haloperidol, pimozide, tiapride) to study the effect of such treatment on hyperkinesia and motor performance. Pimozide and haloperidol improved hyperkinesia; none of the drugs significantly affected motor performance. No correlation was found between the severity of hyperkinesia and motor performance scores, or between hyperkinesia and intelligence score, before and after therapy.